Evaluation of electrospun PLLA-ECM scaffolds as biomaterials for bone regeneration - Burrows, Mariana Carvalho (2016)
The extracellular matrix (ECM) is secreted by the host tissue and is an important key for mechanisms of cell responses. The main properties of the ECM materials include biodegradability, biocompatibility, and nanostructured in a 3D fibre network. In addition, ECM is composed of important molecules like growth factors, glycosaminoglycans (GAGs), collagens, fibronectin, and lamin, while final composition depends on the native tissue. We have selected for this study ECMs from cortical bone (B-ECM) and pericardium (P-ECM) tissue. These ECMs were digested by collagenase, pepsin and trypsin. Each of these digested ECMs was used to produce PLLA-ECM based electrospun scaffolds by two different methodologies (1) non-crosslinked (NCLK) hybrid electrospun scaffolds composed of PLLA and digested ECMs and (2) PLLA-collagen electrospun scaffolds crosslinked with digested ECMs (CLK scaffolds). This research proposes the characterization of the digestion promoted by collagenase, pepsin and trypsin on the ECMs, followed by the evaluation of the potential of the digested ECMs and of the PLLA-ECM scaffolds for bone regeneration. The proteinaceous mixture, produced from the ECM digestion, had compositions, which were dependent on the type of ECM, and on the enzymatic treatment, as shown by protein quantification, GAGs quantification, TGA, SDS-page and TPEF-SHG. All the results point to an extensive digestion caused by collagenase and pepsin and a milder digestion caused by trypsin. The digested ECMs were incorporated into nanofibrous scaffolds, and the products were characterized by SEM, TGA, DSC and TPEF-SHG. The porous nanofibrous mesh from non-crosslinked scaffolds exhibited fibres without beads and a uniform diameter. However, the crosslinked scaffolds presented non-organized agglomerates around the fibres making a less porous surface. TGA and DSC suggest the incorporation of the ECMs on the scaffolds. However, the distribution of the protein on the polymer was mostly dependent on the incorporation method, as showed by TPEF-SHG. To access the biomaterial ability for bone regeneration, bone marrow mesenchymal stem cells (BMMSCs) were cultured on the scaffolds over 21 days. Osteogenic markers such as ALP activity, mineral nodule formation by ARS staining, col1a2 immunostaining, and gene expression were analysed to access how the materials could induce BMMSCs osteodifferentiation. Comparing NCLK to CLK scaffolds the key factor for osteogenesis is the release of soluble factors, showing NCLK scaffolds with a higher ability to induce mineralization than CLK scaffolds. However, when comparing the effect of the enzymatic digestion on the mineralization of the scaffolds over the days, it is possible to establish that the effect of the enzymatic treatment is also related to the type of ECM. Despite all those differences, some PLLA-ECM scaffolds exhibited potential to induce earlier mineralization, observed by the analysis of bglap, runX2, Osx, sparc and col1a2 genes as osteogenic markers.